Predictions of Knowledge Management Effectiveness in Healthcare Organizations - Kisumano, Georges Mumbere (11th International Scholars Conference, 2018)
Having the right knowledge to act and decide has become very crucial in the 21st century and particularly for healthcare organizations where medical errors can cause millions of injuries (Ghosh & Scott, 2006). Effective knowledge management improves the quality of care provided by medical doctors and nurses to patients. This research studied the impact of change readiness, organizational culture, organizational ethical climate, knowledge management process on knowledge management effectiveness in a rural town in Democratic Republic of Congo. A sample of 117 nurses and medical doctors participated in the study. Three main findings were reached. First, change readiness, organizational culture, organizational ethical climate, knowledge management process, and knowledge management effectiveness are significantly related. Second, change readiness and knowledge management processes significantly predicted knowledge management effectiveness. Lastly, knowledge management processes are significantly predicted by organizational ethical climate, change readiness, and organizational culture. Implications of the study were that hospitals should invest in developing knowledge management processes such as knowledge acquisition and foster a culture of learning, risk taking and team working in order to provide appropriate services to patients.